Indigenous tenure security and local participation in climate mitigation programs: Exploring the institutional gaps of REDD+ implementation in the Peruvian Amazon - Dupuits, E.; Cronkleton, P. (Wiley, 2020)
The Reduction of Emissions from Deforestation and forest Degradation (REDD+) mechanism faces implementation challenges related to tenure security and governance institutions. In response, multiple regional climate mitigation initiatives have emerged. In Peru, indigenous networks have created their own Indigenous Amazonian REDD (RIA), an initiative aiming to strengthen property rights for native peoples. At roughly the same time, the Peruvian government launched the National Forest Conservation Program (PNCB), a conditional payment scheme aiming to encourage sustainable forest management. However, these initiatives must still overcome fragmented institutional governance of forests at the regional scale and continued challenges related to indigenous tenure security. This article examines how indigenous federations and the Peruvian government are attempting to implement these initiatives in the Amazonian region of Madre de Dios to examine how challenges play out in practice. These cases illustrate the institutional gaps between national policies, regional capacities, and local needs and expectations. However, it also demonstrates how an innovative institutional partnership at the subnational scale may be overcoming some of these challenges.